Surface Plasmon Assisted Control of Hot-Electron Relaxation Time - Memarzadeh, Sarvenaz; Kim, Jongbum; Aytac, Yigit; Murphy, Thomas E.; Munday, Jeremy N. (2020 Conference on Lasers and Electro-Optics (CLEO), 2020)
Using time-resolved reflection measurements in the Kretschmann configuration under fixed absorbed power, we observe a slowing of the hot-electron relaxation in gold films associated with coupling to surface plasmons.